An Exploratory Interplay of EFL Teachers’ Reflection and Their Teaching and Learning Beliefs - Dehghayedi, Mehdi; Bagheri, Mohammad Sadegh (Universitas Negeri Makassar, 2019)
The main objective behind this study was to investigate the association between EFL teachers’ reflective behavior and their language learning and teaching beliefs. Accordingly, two respective questionnaires were given to 130 male and female EFL teachers who were conveniently sampled, and the elicited data were analyzed via correlational and multiple/multivariate regression analyses. Five components of teachers’ beliefs such as foreign language aptitude, the difficulty of language learning, the nature of language learning, learning and communication strategies and motivation and expectations were taken into account in the analyses. The results indicated that although there is a significant relationship between teachers’ reflectivity and their beliefs on language learning, teachers’ reflection is not a significant predictor for teachers’ beliefs and its constituting components.